Expression of mir-25-3p, CARD9 and Surviving in Acute Pancreatitis and Predictive Value for Patient Outcome: mir-25-3p, CARD9 and surviving for patient outcome - Fang , Nianfu; Ding , Yuanjun; Yang , Weisheng (Cellular and Molecular Biology, 2023)
The clinical data of 246 patients with acute pancreatitis who met the inclusion and exclusion criteria in our hospital from May 2018 to May 2020 were collected as the modeling group, and 96 patients were used as the model validation group. To observe the expression of mir-25-3p, CARD9 and Survivin in patients with acute pancreatitis. To analyze the prognostic factors of acute pancreatitis by univariate and multivariate analysis, and to establish and validate the prognostic model of acute pancreatitis. Results: There was no significant difference in general data between the two groups (P>0.05). Of 246 AP patients, 217 survived and 29 died. The APACHEI score, BISAP score, CRP, lipase, lactate, mir-25-3p, CARD9 and Survivin in the survival group were lower than those in the death group, and the differences were statistically significant (P<0.05). There was no significant difference in other indexes (P>0.05). APACHEI score, BISAP score, CRP, lipase, lactate, mir-25-3p, CARD9 and Survivin were included in multivariate logistic regression analysis. Survival =1 and death =0 were the dependent variables. BISAP score, CRP, lipase, lactate, mir-25-3p, CARD9 and Survivin were all protective factors for the survival of AP patients. Log(P)=-1.648×BISAP score -0.045×CRP-0.013× lipase-0.205 × lactate-1.339 × Mir-25-3P-2.701 ×CARD9-1.663×Survivin+43.925. The survival protective factors of AP patients were incorporated into R software to establish the nomogram prediction model.